Emerging techniques for soil carbon measurements - Milori, D.M.P.B.; Segnini, A.; Silva, W.T.L. da; Posadas, A.; Mares, V.; Quiróz, R.; Martin Neto, L. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Soil carbon sequestration is one approach to mitigate greenhouse gases. However, to reliably assess the quantities sequestered as well as the chemical structure of the soil carbon, new methods and equipment are needed. These methods and equipment must allow large scale measurements and the construction of dynamic maps. This paper presents results from some emerging techniques to measure carbon quantity and stability. Each methodology has specific capabilities and their combined use along with other analytical tools will improve soil organic matter research. New opportunities arise with the development and application of portable equipment, based on spectroscopic methods, as laser-induced fluorescence, laser-induced breakdown spectroscopy and near infrared, for in situ carbon measurements in different ecosystems. These apparatus could provide faster and lower cost field analyses thus improving soil carbon contents and quality databases. Improved databases are essential to model carbon balance, thus reducing the uncertainties generated through the extrapolation of limited data.